English-Indonesian Subtitling of Figurative Language in Final Destination: Bloodlines: An Accuracy and Acceptability Analysis - Arif Sorayaman Hulu; Daniel Sbastian (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Figurative language is central to horror cinema, yet its transfer in subtitling is complicated by the medium's spatial and temporal constraints, and prior studies have often measured accuracy without separating meaning transfer from target-language naturalness. This study investigates the English-to-Indonesian subtitle translation of figurative language in the horror film Final Destination: Bloodlines (2025). Its objectives are to identify how four dominant figurative types are distributed across the corpus, to determine the translation techniques used to transfer them, and to assess subtitle quality using the Functional Equivalence and Acceptability dimensions of Pedersen's (2017) FAR model. Although the FAR model comprises three pillars, the Readability dimension, which concerns technical spotting such as line length and reading speed, is deliberately set aside so that attention remains on the linguistic-semantic transfer of figurative meaning, which the two retained dimensions govern. Employing a qualitative descriptive design supported by quantitative frequency data, the corpus comprises 20 purposively selected segments representing Simile, Metaphor, Personification, and Hyperbole. A second rater validated the data, yielding inter-rater agreement of κ = 0.83 (Cohen's Kappa), within the almost perfect range. The translator relied mainly on Literal Translation (40.0%) and Modulation (40.0%), supplemented by Transposition (15.0%), Amplification (5.0%), and Reduction (5.0%). For quality, 85.0% of expressions achieved Accurate Functional Equivalence, while 15.0% were Less Accurate due to reduced stylistic or supernatural intensity; likewise, 85.0% were Acceptable and 15.0% Less Acceptable due to slight rigidity. The study concludes that while literal translation secures formal correctness, strategic modulation and transposition are crucial for preserving psychological tension and cognitive immersion, and that figurative meaning is most easily weakened at culturally specific images and at the directness of metaphor and personification.